2002
DOI: 10.1093/oxfordjournals.intqhc.a002609
|View full text |Cite
|
Sign up to set email alerts
|

The Leeds University maternity audit project

Abstract: We have documented a massive shift in practice in line with the evidence, although many units still have substantial room for improvement. About 2000 wound infections, 200 deaths due to prematurity, nearly 8000 women in pain from catgut sutures, and 1500 cases of severe perineal trauma from forceps remain preventable. The reasons why units vary remain obscure, although the qualitative interviews often revealed local factors such as key enthusiastic staff. There was no sign of evidence being positively driven i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 12 publications
1
37
0
Order By: Relevance
“…In Thailand, registered nurses with midwifery training usually provide the routine obstetric care. In Thai hospitals, the median number of doctors was 6 (range 3-18) and 5 (2-11) in the intervention and control groups respectively, and the number for nurses were 15 (10-28) and 13 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), respectively. The trial workshops were successfully implemented although the implementation of health sector reform initiatives in Thailand resulted in a prolonged interval (up to 6 months in some) interval between the second and third workshops.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Thailand, registered nurses with midwifery training usually provide the routine obstetric care. In Thai hospitals, the median number of doctors was 6 (range 3-18) and 5 (2-11) in the intervention and control groups respectively, and the number for nurses were 15 (10-28) and 13 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), respectively. The trial workshops were successfully implemented although the implementation of health sector reform initiatives in Thailand resulted in a prolonged interval (up to 6 months in some) interval between the second and third workshops.…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective analysis of obstetric practices in the UK showed substantial shifts over a period of 8 years, although it is not clear when the change took place. 13 There were various barriers, including language in Thailand, that may have contributed to the lack of effect, some of them beyond hospital clinical staff's control 14 . Since our intervention targeted primarily clinical staff, some institutional and other organisational barriers, whether perceived or real, may have impeded change.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 20 UK maternity units found substantial change in practise over 8 years, but few associations between proxy outcomes and other explanatory variables. 49 Earlier in this phase of the study, we considered the beneits and limitations of using case notes as the basis for reviewing quality of care and examined the reliability and value of two review methods -holistic (implicit) review and criterionbased (explicit) review -in the hands of different types of health professional. We showed that the two methods provide different types of quality assessment with reasonable to good levels of reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Such improvements might be partly attributable to wider acceptance of their evidence base. 16 Thus, our ability to produce or detect significant improvements in practice was limited by 'ceiling effects' for two important outcomes, encountered by other investigators. 17 Other potential design weaknesses are unlikely to account for the lack of effect.…”
Section: Discussionmentioning
confidence: 99%